2018
DOI: 10.1177/1753193418813771
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simultaneous steroid injection after percutaneous trigger finger release: a randomized controlled trial

Abstract: The purpose of this study was to test the hypothesis that an improved outcome can be achieved by employing simultaneous steroid injection after percutaneous A1 pulley release. One hundred and twelve digits were randomized to either percutaneous A1 pulley release alone or release of the A1 pulley with a steroid injection. The visual analogue scale score for pain, modified patient global impression of improvement and modified Quinnell grade were assessed at 3 weeks and 3 months after surgery. At 3 weeks, subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
1
16
1
Order By: Relevance
“…Contrary to open pulley release, synovectomy is not possible in percutaneous surgery and may account for this sonographic nding present up to several months postoperatively. Several authors describe the use of concurrent cortisone, which may address this issue 26,27,32 . However, the vast majority of patients in our small case series were asymptomatic despite the presence of this sonographic nding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrary to open pulley release, synovectomy is not possible in percutaneous surgery and may account for this sonographic nding present up to several months postoperatively. Several authors describe the use of concurrent cortisone, which may address this issue 26,27,32 . However, the vast majority of patients in our small case series were asymptomatic despite the presence of this sonographic nding.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been shown that with combined corticosteroid injection during percutaneous release, postoperative swelling has been reduced without more wound healing complications. 26,27 Other complications were only visible in cases that needed conversion to an open procedure and were caused by incorrect placement of the guide instrument or hook knife. After design revision, conversion to an open procedure has been necessary twice as a precautionary measure and we have not seen injuries in these two cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only operation time in the guidance of the ultrasound group was longer [ 33 ]. Compared to these studies, Jegal et al (2018) showed that topical injection of corticosteroids after the percutaneous release can improve treatment outcomes and reduce patient pain in the short period after surgery [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of trigger finger usually is conservative if it is uncomplicated and if it has a short history of symptoms. It includes steroid injections and splinting [2,3,4]. Percutaneous trigger finger release is simple and effective with success rates of 84% to 100% at the mid-term follow-up [4,5,6].…”
Section: Introductionmentioning
confidence: 99%